Effects of zeolite concentrations and slow release fertilizer incorporated in kenaf core fiber media on selected annual flowers - Muhammed, Bilal Adil (2016)
Kenaf core fiber (KCF) could become a good growing substrate as the material is renewable, easy to handle, lightweight and low cost. However, KCF has poor chemical and physical properties due to its low cation exchange capacity (CEC) and wate retention capacity. The study was conducted to determine the effects of different concentrations of zeolite incorporated to KCF on growth and development of some selected annual flowers; to examine and improve the physical and chemical properties of the substrate consisting of KCF by applying different rates of slow- release fertilizer; determine the effects of different rates of slow-release fertilizer on growth and flowering of marigold plants grown on KCF containing different concentrations of zeolite; and finally to determine the effects of KCF containing zeolite on growth and flowering of marigold, celosia, and cosmos plants. This study consists of four experiments. The first experiment was conducted using different concentrations of zeolite (0, 10, 20, 30, 40, and 60 g/L media) incorporated into KCF. The second experiment was conducted using concentrations of zeolite (0, 10, 20, 30 and 40 g/L media) incorporated into KCF using marigold as an experimental plant. The third experiment was conducted in order to improve KCF base substrate media by adding different concentrations of zeolite (0, 30 and 60 g/L media), and slow release fertilizer (Osmocote® applied as pre-plant fertilizer 0, 3, 6, 9 and 12 g/L media) and applied as post-plant fertilizer (0 and 5 g/L media) into KCF media. The last experiment involved different levels of zeolite (30, 60 and 90 g/L media) incorporated to KCF using three species of annual flowers celosia, cosmos and marigold as the plant materials. The experimental units were arranged in Randomized Complete Block Design (RCBD). The results of the first experiment showed that different concentrations of zeolite incorporated to KCF had no significant effect on pH, electrical conductivity (EC), and nitrogen drawdown index (NDI), wettability, container capacity and air filled porosity of the KCF substrate. However, using different concentrations of zeolite significantly affected the CEC of the KCF substrate media for the concentration of 0 g/L compared to other treatments. In the second experiment, different concentrations of zeolite incorporated into KCF significantly affected the plant performance of marigold plants where the highest plant growth and flowering of marigold plant were recorded in media containing 40 g/L media zeolite as reflected by plant height, stem width, flower number and flowers size. In the third experiment, different concentrations of zeolite incorporated into KCF did not have any significant effect on growth and flowering of the marigold plant. However, different concentrations of pre-plant and post-plant fertilizer in KCF affected the growth of marigold significantly. Plants grown on media with 5 g/L slow release fertilizer as a post-plant fertilizer were better than those grown on 0 g/L as indicated by plant height, stem width, and flower sizes. Addition of 12 g/L fertilizer as a pre-plant fertilizer had significantly promoted plant growth in term of plant height, stem width, flower number, and flower sizes. The result of the last experiment showed that, There was no significant effect of using different concentrations of zeolite on the performance and plant growth. However, different species of annual flowers grew differently as shown in their plant height, stem width, flower number and flower sizes. Celosia showed the best growth performance in KCF incorporated with zeolite followed by marigold and cosmos. On the other hand, marigold had the highest dry weight value compared to celosia and cosmos when grown in KCF incorporated with zeolite. Results of the study showed that KCF produced from Hibiscus cannabinus incorporated with different concentrations of zeolite could be used in successful production of annual flowers, especially when the media were treated with slow release fertilizer, both on pre-plant and post-plant applications.